Pengaruh Pemberian Kredit Terhadap Profitabilitas pada PT. Bank Rakyat Indonesia (Persero), Tbk Cabang Ciputat - Tati Rosyati (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to see the effect of Crediting on Return On Assets at PT. Bank Rakyat Indonesia (Persero), Tbk Ciputat Branch. The method used is explanatory research. The analysis technique uses statistical analysis with regression, regression, determination and hypothesis testing. The variable of the results of this study was that the provision of credit obtained an average value of 380.697%. The return on assets variable obtained an average value of 4.337%. Lending has a positive and significant effect on Return On Assets with a regression equation value of Y = 4.555 + 8.794X, and an understanding value of 0.683 or having a strong level of relationship with a determination value of 04.6%. Hypothesis testing obtained a significance of 0.000 <0.05.